Identifying the teaching of English to early young learners at Stepping Stones School Surabaya - Restuti, Margareta Desi (ELT Forum: Journal of English Language Teaching, 2021)
Early stage of human life is considered as unique as it has special characteristics that are different from other stage of human being’s development and growth. There are ways and strategies in dealing with young learners especially at the process of learning. As part of the methods dealing with young learners, school has taken an important role besides the parents of the children. There are many roles taken by school such as teaching in the process of learning of the young learners. In Indonesia, learning English becomes one of important part in the process of learning at the school. And there are notes to be considered in introducing English as a Second Language to young learners. The research was conducted to find out that there are key factors to be considered dealing with teaching English to early young learners and one of the important factors is one of the key factors underlying methods of the teaching English especially at Steping Stones School. The research was conducted at Stepping Stones School Surabaya as it is a school for very young learners. The methods of the research is a qualitative descriptive research. The research found out that the methods of teaching English to young learners need a full English school and a school with fun learning environment. The key factors underlying the methods of teaching English at the Stepping Stones School Surabaya are the school becomes a high quality preschool program with a well-designed curriculum; the school is with well-qualified teachers enabling to interpret the school curriculum to be a daily based practices in teachings; the school pays attention on the age of the students especially in applying the full English method; the school involves the parents to be in part of the learning by having similar ways in treating the children at home.